Socialization and Training to Increase Learning Motivation and Interest in Entrepreneurship Among Students at the Al-Imran Orphanage Foundation, Gowa Regency - Faisal; Wahrini, Retyana (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
This community service activity aims to increase learning motivation and foster entrepreneurial interest among students living at the Al-Imran Orphanage Foundation in Gowa Regency. The background to this activity is based on the low learning motivation and limited access to life skills faced by the orphanage children, as well as the importance of providing entrepreneurial skills as an effort to create economic independence. The method used is a participatory educational approach, which includes four stages: identification of needs, program planning, activity implementation, and evaluation. This activity was carried out through two main sessions: socialization of learning motivation and practice-based entrepreneurship training. The results of the activity showed a significant increase in participants' understanding of the importance of education and the emergence of entrepreneurial interest after participating in the training. Participants demonstrated high enthusiasm, creativity, and courage to try to make and market simple products. In conclusion, this activity has a positive impact on building the learning spirit and entrepreneurial spirit of the orphanage children, and is recommended for ongoing implementation with the support of mentoring and cross-sector collaboration.